Financial Development in Asia : Beyond Aggregate Indicators - Didier, Tatiana; Schmukler, Sergio L. (World Bank, Washington, DC, 2014)
This paper documents the major trends in financial development in Asia since the early 1990s and the spillovers to firms. It compares Asia with advanced and emerging countries and uses both aggregate and disaggregate indicators. Financial systems in Asia remain less developed than in advanced countries but more developed than in Eastern Europe and Latin America. Bond and stock markets play a larger role and institutional investors have gained importance. Nonetheless, capital-raising activity has not expanded. A few large companies capture most of the issuances. Many secondary markets remain illiquid. The public sector captures a significant share of bond markets. The largest advancements in Asia occurred in China and India. But still in these countries, few large companies use capital markets to expand and grow, becoming much larger than nonuser firms. In sum, Asia's financial systems remain less developed than aggregate measures suggest, with few spillovers to many firms.